2020
DOI: 10.1186/s12880-020-00483-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI texture analysis for prediction of BRCA-associated genetic risk

Abstract: Background: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. Methods: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Finally, this study used ROI analysis, but since ovarian cancer is a heterogeneous tumor and the ROIs were set visually, the influence of the ROI settings on the results cannot be denied. For qualitative classification of ovarian tumors, the usefulness of new quantitative parameters of MRI, such as perfusion, 25 , 26 DWI, 27 and texture analysis, 13 , 28 has been reported, and further validation including these parameters is required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study used ROI analysis, but since ovarian cancer is a heterogeneous tumor and the ROIs were set visually, the influence of the ROI settings on the results cannot be denied. For qualitative classification of ovarian tumors, the usefulness of new quantitative parameters of MRI, such as perfusion, 25 , 26 DWI, 27 and texture analysis, 13 , 28 has been reported, and further validation including these parameters is required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on radiomics features of breast MR, which were found to be associated with gene mutations, e.g., HER-2, TP53, PI3K, to different degrees [ [34] , [35] , [36] , [37] ]. Vasileiou and colleagues [ 38 ] utilized 41 breast MRI data to construct a radiomics model for predicting BRCA1/2 mutation and achieved an AUC of 0.865. However, the small sample size indicated inevitable overfitting and relatively low credibility.…”
Section: Discussionmentioning
confidence: 99%
“…A pCR after neoadjuvant chemotherapy is associated with a longer event-free survival (EFS)-the length of time after primary treatment the patient Diagnostics 2023, 13, 372 2 of 15 remains free of disease recurrence-and overall survival (OS) [6,7]. As breast cancer treatment becomes increasingly personalized, artificial intelligence can allow early prediction of pCR through Magnetic Resonance Imaging (MRI) [8], and a hierarchical clustering procedure which offers valuable additional information about data-driven individualized therapies [9,10].…”
Section: Introductionmentioning
confidence: 99%